Analysis of medication errors during anaesthesia in the first 4000 incidents reported to webAIRS. Issue 3 (May 2022) - Kim, Jee Young; Moore, Matthew R; Culwick, Martin D; Hannam, Jacqueline A; Webster, Craig S; Merry, Alan F
Medication error is a well-recognised cause of harm to patients undergoing anaesthesia. From the first 4000 reports in the webAIRS anaesthetic incident reporting system, we identified 462 reports of medication errors. These reports were reviewed iteratively by several reviewers paying particular attention to their narratives. The commonest error category was incorrect dose (29.4%), followed by substitution (28.1%), incorrect route (7.6%), omission (6.5%), inappropriate choice (5.8%), repetition (5.4%), insertion (4.1%), wrong timing (3.5%), wrong patient (1.5%), wrong side (1.5%) and others (6.5%). Most (58.9%) of the errors resulted in at least some harm (20.8% mild, 31.0% moderate and 7.1% severe). Contributing factors to the medication errors included the presence of look-alike medications, storage of medications in the incorrect compartment, inadequate labelling of medications, pressure of time, anaesthetist fatigue, unfamiliarity with the medication, distraction, involvement of multiple people and poor communication. These data add to current evidence suggesting a persistent and concerning failure effectively to address medication safety in anaesthesia. The wide variation in the nature of the errors and contributing factors underline the need for increased systematic and multifaceted efforts underpinned by a strengthening of the current focus on safety culture to improve medication safety in anaesthesia. This will require the concerted and committed engagement of all concerned, from practitioners at the clinical workface, to those who fund and manage healthcare.